CO oxidation on partially oxidized Pd nanoparticles - Libuda, Jörg; et al. (Journal of Catalysis, 2006)
Combining multi-molecular beam (MB) experiments and in situ time-resolved infrared reflection absorption spectroscopy (TR-IRAS), we studied the relationship between the formation of Pd surface oxides and the reaction kinetics of CO oxidation on a well-defined Fe3O4-supported Pd model catalyst. The model catalyst was prepared in-situ under ultra-high-vacuum (UHV) conditions by Pd deposition onto a well-ordered Fe3O4 film on Pt(111). In previous studies, structure, morphology, and adsorption properties of the model system, as well as the formation of I'd oxide species, were characterized in detail. At low reaction temperatures (T < 450 K), the CO oxidation activity of partially oxidized Pd particles was found to be significantly lower than that of metallic Pd particles. We address this deactivation of the catalyst to a weak CO adsorption on I'd surface oxides, leading to a very low reaction probability. Even after extended exposure to CO-rich reactants at 400 K, no significant gain in catalytic activity due to reduction of surface oxides was observed. As a result, we conclude that the formation of Pd oxide species at higher temperatures causes long-term deactivation of the catalyst at lower temperatures. At higher reaction temperatures (T >= 500 K), however, Pd oxides can be dynamically formed and decomposed, depending on the composition of the reactant environment. Although Pd oxides are formed on the surface under O-rich conditions, such oxide species are decomposed under CO-rich conditions at these temperatures. Using a simple model, we qualitatively analyzed. the formation and decomposition process of Pd oxides under reaction conditions. We found that at higher reaction temperatures, partial oxidation of the Pd particles generally led to reduced CO oxidation activity and slow hysteresis effects that were strongly dependent on the pretreatment of the sample. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: model catalysts; surface reaction kinetics; molecular beams; surface oxidation; palladium; iron oxide; CO oxidation